Structural steel plate damage detection using DFT spectral energy and artificial neural network - Paulraj, Murugesa Pandiyan, Prof. Madya Dr.; Mohd Shukri, Abdul Majid; Sazali, Yaacob, Prof. Dr.; Abdul Hamid, Adom, Prof. Madya Dr.; Krishnan, Pranesh R. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/